Preventive effect of nicardipine on hyperplastic changes in venous bypass grafts - GökÇe, özcan; GökÇe, Çi-gdem; Günel, Salih; özden, Akin; Hüseyino?lu, Kemal; UÇar, özcan; Güngen, Yücel (Springer-Verlag, 1993)
Nicardipine is a relatively new calcium channel blocker with important properties that could result in attenuation of the adverse proliferative changes in autogenous vein bypass grafts. In this experimental, randomized, controlled study, the effect of nicardipine on the pathologic findings in aortoaortic bypass grafts was assessed. Forty-two male rabbits (Orycytolagus cuniculus) were randomized to three groups: group 1 received nicardipine and groups 2 and 3 placebo for 4 weeks, after which an aortoaortic bypass was realized with an autogenous inferior vena cava segment. During the following 4 weeks, groups 1 and 2 received nicardipine, and placebo was continued in group 3. The animals were sacrificed at the end of the study to permit removal and evaluation of the bypass grafts. The mean intimal and medial thickness values for groups 1 and 2 were lower than those for group 3, indicating that nicardipine has a significant preventive effect on the hyperplastic changes in venous bypass grafts compared to placebo. The mean intimal and medial thickness values of group 1 were also lower than those of group 2, and the differences carried statistical relevance, suggesting that the use of nicardipine before grafting could potentiate its protective effect. To provide stimulus for further research, an attempt is made to relate the hyperplasia-preventing effect of nicardipine to possible mechanisms. © 1993 Société Internationale de Chirurgie.
Keywords: Animal; Aorta; Hyperplasia; Male; Nicardipine; Rabbits; Random Allocation; Vena Cava, Inferior; 1,4 dihydropyridine derivative; nifedipine; animal model; article; autograft; controlled study; graft occlusion; hyperplasia; male; nonhuman; oral drug administration; rabbit; vein bypass; vein graft